2016
DOI: 10.1097/olq.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Higher HPV16 and HPV18 Penile Viral Loads Are Associated With Decreased Human Papillomavirus Clearance in Uncircumcised Kenyan Men

Abstract: Background Whether higher penile human papillomavirus(HPV) viral load is associated with a lower rate of HPV clearance remains unknown. Objectives We examined the association between penile HPV16 and HPV18 viral load and subsequent HPV clearance in uncircumcised Kenyan men. Study Design Participants were HIV-seronegative, sexually active, 18–24 year old men randomized to the control arm of a male circumcision trial in Kisumu, Kenya. Men provided exfoliated penile cells from two anatomical sites (glans/coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Decreased viral “ shedding ” among men was suggested as a reason for the reduced acquisition of HPV in female partners of the circumcised men (160). In uncircumcised men with a high viral load, clearance of high-risk HPV16 and HPV18 was lower, thus increasing risk of HPV transmission to female partners (112). In addition to the lower risk of oncogenic HPV infection, female partners of circumcised men in the Ugandan RCT had lower HPV viral loads that were contributed entirely by incident new high-risk HPV infections during the 24 months follow-up period (PRR = 0.66; 95% CI 0.50–0.87, P = 0.003) (113).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased viral “ shedding ” among men was suggested as a reason for the reduced acquisition of HPV in female partners of the circumcised men (160). In uncircumcised men with a high viral load, clearance of high-risk HPV16 and HPV18 was lower, thus increasing risk of HPV transmission to female partners (112). In addition to the lower risk of oncogenic HPV infection, female partners of circumcised men in the Ugandan RCT had lower HPV viral loads that were contributed entirely by incident new high-risk HPV infections during the 24 months follow-up period (PRR = 0.66; 95% CI 0.50–0.87, P = 0.003) (113).…”
Section: Resultsmentioning
confidence: 99%
“…Higher viral load was also associated with decreased HPV clearance rates in uncircumcised males and homosexual men who smoke 40, 41 . Methylation of CpG sites in HPV DNA is a marker of persistent infection, particularly for HPV-16, that may have utility in triage: in a large randomised controlled trial, methylation triage on cervicovaginal self samples was non-inferior to cytology triage on clinician-taken samples for the detection of high-grade CIN 42 .…”
Section: Advances In Screeningmentioning
confidence: 92%
“…Recently, the predictive value of HPV viral load as a measure of persistence has been investigated: several studies have shown that high baseline HPV-16 and -18 viral load or viral load increase over time are associated with persistent infections 34 36 and low viral load, or a >100-fold decline over time, is associated with clearance 37 39 . Higher viral load was also associated with decreased HPV clearance rates in uncircumcised males and homosexual men who smoke 40 , 41 . Methylation of CpG sites in HPV DNA is a marker of persistent infection, particularly for HPV-16, that may have utility in triage: in a large randomised controlled trial, methylation triage on cervicovaginal self samples was non-inferior to cytology triage on clinician-taken samples for the detection of high-grade CIN 42 .…”
Section: Advances In Screeningmentioning
confidence: 92%
“…Moreover, a cutoff value of 22,000 copies/10 3 cells permits to identify among HPV16 infected women those with a high grade lesion with a specificity of 90% [20] . Furthermore, HPV16 load may represent a risk factor for persisting infection [25] , [26] , [27] , [28] or progression toward a high grade cervical lesion [29] , [30] . In a retrospective longitudinal study, a HPV16 viral load of 200 copies/10 3 cells was shown to represent a relevant cutoff above which women with no or mild abnormalities of the cervix present a high risk to develop an incident CIN2/3 at 18 months [29] .…”
Section: Introductionmentioning
confidence: 99%